2007
DOI: 10.1590/s1516-89132007000300017
|View full text |Cite
|
Sign up to set email alerts
|

Influence of static magnetic fields on S. cerevisae biomass growth

Abstract: Biomass growth of Saccharomyces cerevisiae DAUFPE-1012 was studied in eight batch fermentations exposed to steady magnetic fields (SMF) running at 23ºC (± 1ºC), for 24 h in a double cylindrical tube reactor with synchronic agitation. For every batch, one tube was exposed to 220mT flow intensity SMF, produced by NdFeB rod magnets attached diametrically opposed (N to S) magnets on one tube. In the other tube, without magnets, the fermentation occurred in the same conditions. The biomass growth in culture (yeast … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 10 publications
1
8
0
Order By: Relevance
“…It proved that the growth of biomass was accelerated in samples with PEF-treated inocula. Similar effects were observed in a previous study of the static magnetic field effect on S. cerevisiae biomass growth [3], in which magnetized yeasts showed accelerated kinetics of fermentation and higher biomass growth rate.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…It proved that the growth of biomass was accelerated in samples with PEF-treated inocula. Similar effects were observed in a previous study of the static magnetic field effect on S. cerevisiae biomass growth [3], in which magnetized yeasts showed accelerated kinetics of fermentation and higher biomass growth rate.…”
Section: Resultssupporting
confidence: 89%
“…The optimum ultrasonic treatment at the frequency of 25 kHz resulted in a 15.6% ethanol concentration while ethanol concentration in the control system was lower ([Y] ≈ 12.0%). The positive influence of static magnetic fields (SMF) on the growth of S. cerevisiae biomass was also demonstrated [3]. The biomass (g/L) increment in eight samples, exposed to SMF treatment, was 2.5 times greater after their 24 h fermentation at 23°C than that of the control cultures.…”
Section: Introductionmentioning
confidence: 86%
“…Regarding the biomass concentration S. cerevisiae, some authors have observed stimulatory effects using others MF and exposure times. Picho and Povalyaeva (1996) achieved 12% increase in biomass concentration of 100 mT for 0.67 h, which was also by Mehedintu and Berg (1997) 25% (0.2 mT and 10 h), Motta et al (2001) 1.84% (220 mT and 24 h), Zapata et al (2005) 14.4% using 0.002 mT for 30 s. Muniz et al (2007) studied the growth of S. cerevisiae DAUFPE-1012 when exposed to MF (220 mT). The biomass growth rate increased 2.5 times in relation to un-exposed culture.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, a large number of evidences about the interactions between static magnetic field and/or electromagnetic field with living systems have been reported [2,[11][12][13][14]. There is a general agreement that depending on the magnetic field intensity, it can stimulate or adversely inhibit the cell growth [1,2,[15][16][17][18][19][20][21][22][23][24][25][26], or affect the metabolite production such as the ethanol [1,3,4]. For example, da Motta et al [1] studied the effects of exposure to 220-mT steady magnetic fields (SMF) at 23 ± 1°C, during ethanol production by Saccharomyces cerevisiae.…”
Section: Introductionmentioning
confidence: 99%